Cross-laminated timber connections assembled with a combination of screws in withdrawal and screws in shear. (1st August 2018) - Hossain, Afrin; Popovski, Marjan; Tannert, Thomas
Highlights: 3-ply CLT panels connected with self-tapping screws were tested in shear. Joints with screws loaded in shear exhibit high ductility but low stiffness. Joints with screws loaded in withdrawal are very stiff but brittle. Combining these screws leads to joints with high stiffness and high ductility. Under reversed cyclic loading, all performance values are reduced by up to 40%. Abstract: The research presented in this paper examines the performance of 3-ply cross-laminated timber (CLT) panels connected with self-tapping screws (STS). Half-lap joints with STS loaded in either shear or withdrawal along with an innovative solution combining these two approaches were evaluated in a total of 24 quasi-static monotonic and 15 reversed cyclic tests. The CLT joint performance was evaluated in terms of load-carrying capacity, yield strength, deformation capacity, stiffness, and ductility. The results demonstrated that joints with STS loaded in shear exhibit high ductility but low stiffness, whereas joints with STS in withdrawal are very stiff but brittle. Combining STS that act in shear with STS that act in withdrawal can lead to connections with high stiffness and high ductility. The performance of STS shear connections under reversed cyclic loading is comparable to that of these connections under quasi-static loading; however, all performance values are reduced by up to 40% demonstrating the necessity to provide designers and engineers with connection performance data under cyclic loading for reliable seismic design.